Karl Barth and the liberation theology: Directions for Christian ethics today - Zeferino, Jefferson (Vox Scripturae - Revista Teológica Internacional, 2014)
This paper is about Christian ethic in the background of the theology of Karl Barth. In this way, considering the reality of the post-modern world that the nowadays Christian man is within, Barth’s impulses are sought to help this man in his task to be a real Christian. The starting point of this paper is Karl Barth’s social-political thinking recognized in the articles The Christian in the society and Christian community and Social community, texts that provide some central thesis of his thinking about this theme. With the objective to receive some impulses of his theological construction other theological thinking is examined to know how this reception process was and what is possible to learn with it. So, in this inquiry, the reception of Karl Barth’s thinking in liberation theology is analyzed. All these steps converge in some perspectives to the post-modern Christian man today acting.
Keywords: Karl Barth; Social-political thought; Liberation Theology; Ethics